Membumikan Pemikiran Islam Modern Dalam Framework Pemikiran Syaikh Muhammad Al-Ghozali - M Fadholi; Mochammad Fauzi (LPPM Institut Agama Islam Al-Hikmah Tuban, 2019)
Abstract: The struggle of Islamic thought with the dynamics of social reality, always giving birth to tensions that at the end not only create challenges for Muslims (who care about the position of Islam vis-à-vis) in their social reality, but also can create intellectual and social conflicts among Muslims as a whole. This condition often gives rise to various typologies of various thoughts in Islam. The wave (read: movement) of the Islamic thoughts that blaring loudly in the Islamic world proves that Islam as a discourse will experience an unstoppable diaspora. This condition often gives rise to various typologies of various thoughts in Islam. The wave (read: movement) of the Islamic thoughts that blaring loudly in the Islamic world proves that Islam as a discourse will experience an unstoppable diaspora. In this context, renewal of Islam has logical consequences for a critical review and review of existing Islamic ideologies, both concerning the cultural and aqeedah fields, including Islamic education. The above fact ushered in the presence of the character Shaikh Muhammad Ghozali in his thoughts. Thus, this paper is focused on discussing several things: 1) the historicity of Shaikh Muhammad Ghozali's life, 2) the geology and style of thought, 3) the project of Shaikh Muhammad Ghozali's thinking 4) to know Shaikh Muhammad Ghozali's work on renewal. Keyword: Shaykh Muhammad al Ghozali, Islamic thought, modern